THE STRUCTURE OF NOVEL LINTANG PANJER RINA BY DANIEL TITO AND THE POSSIBILITY OF LEARNING IN SENIOR HIGH SCHOOL - Kartikawati, Dwi Apriana; Widiyono, Yuli (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2022)
The problems discussed are the structural elements of the novel Lintang Panjer Rina and the possibility of learning in high school. The purpose of this research is to describe the building blocks of the novel Lintang Panjer Rina by Daniel Tito and to describe the possibility of learning in high school. The theory used in this research is the structural theory of Burhan Nurgiyantoro. The structural theory is used to analyze the elements of literary works in the novel Lintang Panjer Rina which include: theme, characterization, plot, setting, point of view of storytelling, language style, and moral elements. The collection technique used was library technique and note-taking technique. The data analysis technique used the content analysis technique which examines and discusses the structural elements in the novel Lintang Panjer Rina by Daniel Tito. In the discussion of the data, it is found that the structural elements in the novel Lintang Panjer Rina by Daniel Tito include (1) the theme, namely the return of true love, (2) characters, namely the main character Harjito, while the additional characters are Winarsih, Sumardi, Winarsih’s mother, Warni, Joko, and Om Beng. The characterizations are focused on Harjito’s character, namely a man who doesn’t like making promises, smart, and hardworking, (3) the plot is straight or forward, the events are arranged chronologically, (4) there are three kinds of settings, namely the setting of the place, the setting of time, and social setting, (5) the center of the story is used from the point of view of the omniscient third person. The author becomes an omniscient observer, (6) learning the novel Lintang Panjer Rina in accordance with the KTSP (Education Unit Level Curriculum), which consists of objectives, materials, methods, steps, learning resources, time, and evaluation.